Bridging ecology and physics: Australian fairy circles regenerate following model assumptions on ecohydrological feedbacks. (21st September 2020) - Getzin, Stephan; Erickson, Todd E.; Yizhaq, Hezi; Muñoz‐Rojas, Miriam; Huth, Andreas; Wiegand, Kerstin
Abstract: So‐called fairy circles (FCs) comprise a spatially periodic gap pattern in arid grasslands of Namibia and north‐west Western Australia. This pattern has been explained with scale‐dependent ecohydrological feedbacks and the reaction‐diffusion, or Turing mechanism, used in process‐based models that are rooted in physics and pattern‐formation theory. However, a detailed ecological test of the validity of the modelled processes is still lacking. Here, we test in a spinifex‐grassland ecosystem of Western Australia the presence of spatial feedbacks at multiple scales. Drone‐based multispectral analysis and spatially explicit statistics were used to test if grass vitality within five 1‐ha plots depends on the pattern of FCs that are thought to be a critical extra source of water for the surrounding matrix vegetation. We then examined if high‐ and low‐vitality grasses show scale‐dependent feedbacks being indicative of facilitation or competition. Additionally, we assessed facilitation of grass plants for different successional stages after fire at fine scales in 1‐m 2 quadrats. Finally, we placed soil moisture sensors under bare soil inside the FC gap and under plants at increasing distances from the FC to test if there is evidence for the 'infiltration feedback' as used in theoretical modelling. We found that high‐vitality grasses were systematically more strongly associated with FCs than low‐vitality grasses. High‐vitality grasses also had highly aggregated patterns at short scales being evidence of positive feedbacks while negative feedbacks occurred at larger scales. Within 1‐m 2 quadrats, grass cover and mutual facilitation of plants was greater near the FC edge than further away in the matrix. Soil moisture after rainfall was lowest inside the FC with its weathered surface crust but highest under grass at the gap edge, and then declined towards the matrix, which confirms the infiltration feedback. Synthesis . The study shows that FCs are a critical extra source of water for the dryland vegetation, as predicted by theoretical modelling. The grasses act as 'ecosystem engineers' that modify their hostile, abiotic environment, leading to vegetation self‐organization. Overall, our ecological findings highlight the validity of the scale‐dependent feedbacks that are central to explain this emergent grassland pattern via the reaction‐diffusion or Turing‐instability mechanism. Abstract : Spatially periodic vegetation patterns of drylands have been extensively modelled by physicists based on ecohydrological feedbacks and the reaction‐diffusion or Turing mechanism. A detailed ecological test of the validity of such processes, however, is still pending. Based on the Australian fairy circles, we show that short‐range positive and long‐range negative feedbacks between plants are indeed explaining such emergent vegetation patterns.